Pengaruh Media Sosial terhadap Pembentukan Karakter Remaja dalam Perspektif Pendidikan Islam - Dimas Aryo Seto; Bagas Mahesa; Ananda Saputra; Muftyan Mulya Achmad; Muhammad Dani Setiawan; Ismail Mubarok (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the influence of social media on the character development of adolescents from an Islamic education perspective. The research method used is a descriptive qualitative approach in the form of a literature review. Data were obtained through a review of various scientific sources, such as journals, books, and previous studies related to social media, character education, and Islamic education. Data analysis was conducted using content analysis through the stages of data reduction, data grouping, interpretation, and drawing conclusions. The results of the study indicate that social media has both positive and negative impacts on adolescent character. Positive impacts include ease of accessing information, learning tools, a medium for da’wah, as well as the development of creativity and communication. The negative impacts include a decline in moral values, cyberbullying, consumerist behavior, weak self-control, and a decrease in social interaction. Therefore, Islamic education plays a crucial role in shaping adolescents’ character through the reinforcement of moral values, digital literacy, and supervision from families, schools, and the community.